Adult Learning and Pragmatic Identity Theory - Davin J Carr-Chellman; Joseph Levitan (Adult Education Research Conference, 2016)
The interaction between identity and learning has been under theorized. American Pragmatism offers important insights into identity and learning. With new educational experiences, adults take on new identities. Pragmatic Identity Theory will be an analytical lens allowing us to better understand the identity negotiation within learning experiences.
Keywords: American Pragmatism; Adult Learning; Identity